The Concept of Cultural Journalism: What the Editors in Latvia Think They Do When Doing Cultural Journalism - Skulte, Ilva (Žurnalistikos tyrimai, 2015)
Cultural journalism is a matter of current discussions in journalism theory and practical research. As a relatively small and specific area of journalistic practice, it operates in the intersection between media, culture in general, and arts and creative industries. The complexity, heterogeneity and variability of the field is determined by the major changes transforming all three intersecting areas – the new media, diversity of genres and the audience practices that characterize contemporary communication; liquidity and hybridity is a mark of the global postindustrial society, whereas art is more and more framed by the rise and convertibility of the concepts of creative class, production, and capital. The self-reflection, conceptualisation of their work and the object of report and reference – culture – by the editors and producers from the Latvian cultural media outlets and departments is the topic of this paper. The main conclusions are that their concepts of culture, cultural quality, and journalistic production, as well as the goals and principles of their work largely differ depending on the type and format of their medium. However, what unifies most of the respondents is the lack of more abstract conceptualisation of the complexity of the field and its social contexts with all the potential consequences for their work and the field of culture in general.
Keywords: cultural journalism; arts journalism; culture; self-reflection; autonomy